Speech Genres and Interpretation of the Qur’an - Stewart, Devin J. (Religions, 2021)
This essay provides an overview of the investigation of genres in Qur’anic studies to date and argues for the utility of the theory of speech genres for the interpretation of the Qur’an generally. Drawing on this approach, it addresses several Qur’anic passages whose interpretation has been a matter of debate. Attention to the generic conventions of the various types of speech that are contained in Islam’s sacred text may help resolve a number of long-standing and current interpretive debates.